Anti-tumor necrosis factor α: originators versus biosimilars, comparison in clinical response assessment in a multicenter cohort of patients with inflammatory arthropathies - C. Gioia; A. Picchianti Diamanti; R. Perricone; M.S. Chimenti; A. Afeltra; L. Navarini; A. Migliore; U. Massafra; V. Bruzzese; P. Scolieri; C. Meschini; M. Paroli; et al. (PAGEPress Publications, 2023)
Objective. To compare etanercept and adalimumab biosimilars (SB4 and ABP501) and respective bioriginators in terms of safety and efficacy in a real-life contest. Methods. We consequently enrolled patients affected by rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis, treated with SB4, and ABP501, or with corresponding originators, belonging to the main biological prescribing centers in the Lazio region (Italy), from 2017 to 2020. Data were collected at recruitment and after 4, 8, 12, and 24 months of therapy. Results. The multicenter cohort was composed by 455 patients treated with biosimilars [SB4/ABP501 276/179; female/male 307/146; biologic disease-modifying anti-rheumatic drug (b-DMARD) naïve 56%, median age/ interquartile range 55/46-65 years] and 436 treated with originators (etanercept/adalimumab 186/259, female/ male 279/157, b-DMARD naïve 67,2%, median age/interquartile range 53/43-62 years). No differences were found about safety, but the biosimilar group presented more discontinuations due to inefficacy (p<0.001). Female gender, being a smoker, and being b-DMARD naïve were predictive factors of reduced drug survival (p=0.05, p=0.046, p=0.001 respectively). The retention rate at 24 months was 81.1% for bioriginators and 76.5% for biosimilars (median retention time of 20.7 and 18.9 months, respectively) (p=0.002). Patients with remission/low disease activity achievement at 4 months showed a cumulative survival of 90% to biosimilar therapy until 24 months (p=0.001); early adverse reactions instead represented a cause of subsequent drug discontinuation (p=0.001). Conclusions. Real-life data demonstrated a similar safety profile between biosimilars and originators, but a reduced biosimilar retention rate at 24 months. Biosimilars could be considered a valid, safe, and less expensive alternative to originators, allowing access to treatments for a wider patient population.